"My Kids Will Always Be around Me, if Not Physically, Spiritually They Will Always Be around Me": Fathers in Forensic Inpatient Care. Issue 2 (15th March 2022) - Wells, Michelle; Hartwright, Christopher; Morgan, Sara; Gale, Leigh
ABSTRACT: The current study aimed to increase understanding of men's experiences of fatherhood in forensic inpatient care; a population overlooked in research and at risk of neglect in clinical practice. Eight participants recruited from forensic inpatient services were interviewed. Data was analyzed via social constructivist Grounded Theory. The central psychological concept developed was that of paternal connection, reflecting a transient sense of connection to the father-child relationship. Core categories included 1) Psychological Processes, 2) Interpersonal Relationships, and 3) Institutional Organization. Fathers in forensic inpatient care experience dynamic psychological connectivity to their paternal relationship, regardless of child contact. This multi-layered experience requires responsive intervention to support fathers in this context. Recommendations for research, practice, and policy are outlined.